Factors That Influence Farmers' Decisions in Accessing Farm Business Credit at BRI Bank (Case Study: Rabuhit Village, Gunung Maligas District, Simalungun Regency) - Roeskani Sinaga; Ramainim Saragih; Apriliya Sapitri; Martua Siadari; Jhonson A Marbun (Program Studi Akuntansi Universitas Simalungun, 2026)
This study was conducted in Rabuhit Village, Gunung Maligas District, Simalungun Regency, with three primary objectives: (1) to identify the factors influencing farmers' decisions to access agricultural business credit from BRI Bank; (2) to determine the most dominant factors affecting farmers' decisions to obtain agricultural business credit in Rabuhit Village; and (3) to examine the reasons why some farmers access agricultural business credit while others do not. Data were collected through observation, interviews, and structured questionnaires. The study involved 30 respondents, consisting of 20 farmers who had accessed agricultural business credit and 10 farmers who had not. The respondents were selected based on the following criteria: active farmers residing in Rabuhit Village, aged between 18 and 65 years, owning or cultivating either self-owned or rented agricultural land, and willing to provide the information required for the study. The data were analyzed using multiple linear regression analysis and descriptive percentage analysis. The results of the study indicate that: (1) the factors significantly influencing farmers' decisions to access agricultural business credit from BRI Bank are income and farming experience; (2) among the variables examined, income and farming experience are the most dominant factors affecting farmers' decisions to access agricultural business credit; and (3) the primary reasons farmers in Rabuhit Village access agricultural business credit are insufficient working capital and financial difficulties resulting from crop failure. In contrast, farmers who do not access agricultural business credit generally cite the lack of acceptable collateral and the availability of sufficient business capital as the main reasons for not applying for credit